GAMBARAN PENGETAHUAN, SIKAP, DAN TINDAKAN MAHASISWA JURUSAN FARMASI POLTEKKES KEMENKES MEDAN TERHADAP PENCEGAHAN COVID-19 - Ahmad Purnawarman Faisal; Nurul Hidayah; Adhisty Nurpermatasari; Riza Vahlevi Wakidi; Zulfi Ismaniar Fauzi; Pratiwi Rukmana Nasution (Poltekkes Kemenkes Medan, 2021)
Coronavirus 2019 or COVID-19 is a pandemic that has resulted in high mortality rates in various parts of the world. Good knowledge about the COVID-19 pandemic and clean and healthy living behavior as an effort to prevent the transmission of COVID-19 is important to implement. The purpose of this study was to describe the knowledge, attitudes, and actions about COVID-19 among students of the Department of Pharmacy, Poltekkes, Ministry of Health, Medan. This research method uses a descriptive survey with simple random sampling technique. The characteristics of the respondents, totaling 146 people, were obtained online with the criteria for male-female 111 people and male 34 people. For the level of knowledge, the most answered statements for positive statements were statements Strongly Agree (SS) by 70.5%, namely the statement